Pengaruh Kadar Polietilen Glikol (PEG) 400 terhadap Pelepasan Natrium Diklofenak dari Sediaan Transdermal Patch Type Matriks - Aditya Fridayanti; Esti Handayani; Isnaeni Isnaeni (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2010)
The sodium diclofenac realeased from transdermal patch of combination of EC N–20 and PVP K–30 with ratio 6:4 with plasticizer PEG 400 5% (formula 1), PEG 400 10% (formula 2) and PEG 400 20% (formula 3) was investigated. The percentage of moisture contents was calculated as a difference between initial and final weight with respect to final weight. The homogeneity of patch surface was determined using fluorescence microscope and scanning electron microscope (SEM). Released test using dissolution apparatus were carried out in 500 mL of phosphate buffer saline pH 7.4 ± 0.05 at temperature 37 ± 0.5°C with speed of swirl 50 rpm. Results were analyzed by statistic programmed of SPSS using one way analysis of variance with degree of believed 95% (α = 0,05), showed that that the combination of EC N–20 and PVP K–30 at ratio 6:4 with plasticizer PEG 400 5% was the best choice for manufacturing transdermal patch based on physicochemical and the release profile. ABSTRAK Telah dilakukan penelitian pelepasan sodium diklofenak dari transdemal Patch kombinasi matriks EC N–20 dan PVP K–30 dengan rasio 6:4 dan plasticizier PEG 400 5 % (formula 1), PEG 400 10% (formula 2), dan PEG 400 20 %. Persentase kadar air dihitung sebagai perbedaan antara berat awal dan akhir. Homogenitas dari permukaan Patch di determinasi menggunakan Mikroskop flourescence dan SEM. Uji pelepasan dilakukan menggunakan alat uji dissolusi dalam 500 mL larutan salin fosfat buffer pH 7.4 ± 0.05 pada suhu 37 ± 0.5°C dengan kecepatan pengadukan 50 rpm. Hasil di analisis menggunakan program statistik SPSS analisis one way variance (ANAVA) dengan tingkat kepercayaan 95% (α = 0,05), menunjukkan bahwa kombinasi dari EC N–20 and PVP K–30 pada rasio 6:4 dengan plasticizer PEG 400 5% merupakan pilihan terbaik untuk industri Patch transdemal berdasarkan fisikokimia dan profil pelepasan.